Uczony jako intelektualista publiczny. Przykład religioznawstwa - Sztajer, Sławomir (Człowiek i Społeczeństwo, 2021)
The article discusses the role of public intellectuals, with particular emphasis on scholars specializing in the study of religions. While various functions and aims of public intellectuals are taken into account, the article focuses primarily on risks related to scholars’ engagement in public discourse. The history of the academic study of religion shows that many of its representatives were involved in various ideological endeavors, including political ideologies. It is argued that the main role of the public intellectual in the study of religion is not to be a functionary of religious institutions nor even an interpreter of religious traditions, but a critical researcher who impartially popularizes knowledge about religions and highlights the mechanisms underlying the dynamics of the religious world.